Adolescents and young adults with newly diagnosed Type 2 diabetes demonstrate greater carotid intima‐media thickness than those with Type 1 diabetes. Issue 1 (4th December 2013) - Gu, W.; Huang, Y.; Zhang, Y.; Hong, J.; Liu, Y.; Zhan, W.; Ning, G.; Wang, W.
Abstract Aim To compare the carotid intima‐media thickness in patients with newly diagnosed Type 1 or Type 2 diabetes ranging from 14 to 30 years of age. Methods Demographic, anthropometric and laboratory data were obtained from 404 adolescents and young adults (103 subjects with Type 1 diabetes, 94 with Type 2 diabetes, 153 obese subjects and 54 normal control subjects). Carotid intima‐media thickness was assessed based on Doppler ultrasound examination and compared among the four groups. Results Our data showed significant increases in carotid intima‐media thickness in subjects with Type 1 diabetes, Type 2 diabetes and obese subjects compared with the control subjects, with those in the group with Type 2 diabetes demonstrating the greatest change (P < 0.001). Age, BMI, percentage of fat, waist–hip ratio and total triglycerides were significantly correlated with both common and internal carotid intima‐media thickness segments. From a stepwise multiple linear regression model, the independent determinants of common carotid intima‐media thickness were age, BMI, HbA1c and HDL cholesterol (adjusted R2 = 0.152, P < 0.001). After adjustment for age, sex and HbA1c, the odds ratio for increased carotid intima‐media thickness was 1.67 (95% CI 1.19–2.33, P = 0.003) for obese subjects, 2.38 (95% CI 1.59–9.47, P = 0.001) for subjects with Type 1 diabetes and 3.93 (95% CI 1.90–6.07, P = 0001) for subjects with Type 2 diabetes compared with the control subjects. Conclusions Compared with young control subjects, we found significant increases in carotid intima‐media thickness in patients with newly diagnosed Type 1 diabetes and Type 2 diabetes, with patients with Type 2 diabetes showing greater carotid intima‐media thickness. Traditional cardiovascular risk factors, such as obesity, dyslipidaemia, hypertension and hyperglycaemia, could cause vessel changes even in adolescents and young adults.